Integration of Fuzzy AHP with Other Fuzzy Multicriteria Methods: A State of the Art Survey - Kahraman, Cengiz; Onar, Sezi Cevik; Oztaysi, Basar; Seker, Sukran; Karasan, Ali (OLD CITY PUBLISHING INC, 2020)
AHP is the most widely used multi-criteria decision making method (MCDM) for selection among alternatives in the literature. AHP can be used as a standalone decision making method or it can be used by integrating with another method in selection problems. Vagueness and impreciseness in the data, especially when linguistic data used, can be captured by fuzzy sets. Extensions of fuzzy sets such as hesitant fuzzy sets, intuitionistic fuzzy sets, and spherical fuzzy sets have been often employed in decision making modeling. In this paper, we present a state of the art survey of fuzzy extensions of AHP when it is integrated with another fuzzy MCDM method such as fuzzy VIKOR, fuzzy TOPSIS, fuzzy ELECTRE, fuzzy PROMETHEE, fuzzy, EDAS, fuzzy CODAS, fuzzy COPRAS, fuzzy TODIM, fuzzy MULTI-MOORA, fuzzy MABAC, and fuzzy WASPAS. Graphical and tabular illustrations are given to summarize the results of the literature survey.
Keywords: fuzzy AHP; fuzzy VIKOR; fuzzy TOPSIS; fuzzy ELECTRE; fuzzy PROMETHEE; fuzzy; EDAS; fuzzy CODAS; fuzzy COPRAS; fuzzy WASPAS; fuzzy TODIM; fuzzy MULTIMOORA; fuzzy MABAC; CRITERIA DECISION-ANALYSIS; VALUED NEUTROSOPHIC AHP; EDAS METHOD; VIKOR METHOD; SELECTION; PROMETHEE; WASPAS; MODEL; EXTENSION; CONSISTENCY; Computer Science; Science & Technology - Other Topics